Toward a new growth pole for the world: Rethinking the strategies for Huaihua International Inland Port in China - Lv, Lu; Hou, Tengteng; Shu, Xiaohui; Tian, Robert Guang (Edelweiss Applied Science and Technology, 2024)
This article aims to analyze the existing Huaihua International Inland Port studies and regional economic development. On this basis, the strategic positioning of the port is redefined, and its impact on the economic growth of China and the world is examined. Furthermore, the article explores the port’s main challenges under the Belt and Road Initiative and proposes sustainable and healthy development strategies. It demonstrates that in the era of globalization, the importance of international trade and logistics has become increasingly prominent. As the world’s second-largest economy, China’s solid internal logistics infrastructure and well-developed transportation systems are vital to maintaining and expanding its economic vitality. It finds that the Huaihua International Inland Port is integral to China’s Western Development Strategy and has become an essential hub connecting Western China with international markets. The port profoundly impacts the economic vitality of Huaihua and surrounding areas, promoting employment and improving residents’ living standards. However, it also faces many challenges in its development. It suggests that the port administrative team needs to improve operational efficiency, efficiently coordinate various modes of transportation, attract more industries, and balance economic development and environmental protection. Based on the in-depth analysis indicates the strategic orientations and recommendations for the future development of the port. At the same time, it is expected to provide a reference for other regional economic development projects.